Performance analysis of differential-frequency microgyroscopes made of nanocrystalline material. (November 2017) - Ghommem, M.; Abdelkefi, A.
Highlights: Modeling of vibrating beam microgyroscopes made of nanocrystalline material. Quasi-static and coupled dynamic analysis of rotating microbeams subject to electric actuation for gyroscopes operating in frequency mode. Performance analysis of differential-frequency microgyroscopes. Design enhancement of microgyroscopes. Graphical abstract: Abstract: The performance of a microgyroscope consisting of a rotating microbeam made of nanocrystalline silicon connected to a proof mass and subjected to electric actuation is investigated. The microgyroscope is assumed to operate in frequency-based mode; that is, the measurement of the rotation rate is extracted from the shift in the frequency response along the drive and sense directions. Closed-form expressions of the natural frequencies and mode shapes of the coupled dynamical system are derived. The onset of the base rotation is observed to split the common natural frequency of the two bending modes into a pair of closely-spaced natural frequencies. This frequency shift used as the output parameter detecting the rotation rate. A sensitivity analysis of this parameter to the rotation rate when varying the material properties of the microbeam and electric actuation is then performed. When applying the same DC voltage for the drive and sense modes, the differential frequency is found to vary linearly with the base rotation. Incorporating the fringing field in the electrostatic forcing and varying the grain size of the nanocrystalline silicon have insignificant impact on the calibration curve for this case. Breaking the symmetry of the microgyroscope in terms of the applied DC voltage along the drive and sense directions is observed to reduce significantly the sensitivity of the differential frequency to the base rotation rate. The larger the DC voltage bias is, the lower the sensor sensitivity is. Furthermore, under these operating conditions, the results show that the variations of the differential frequency with the rotation rate undergo nonlinear trends. Considering higher order modes is found to reduce the impact of the DC voltage bias on the calibration curve of the microgyroscope.